An R-package to boost fitness and life expectancy of environmental models. (October 2017) - Kneis, David; Petzoldt, Thomas; Berendonk, Thomas U.
Abstract: Ordinary differential equations (ODE) are at the center of many environmental models. The R software is increasingly used to implement ODE-based models boosted by add-on packages providing numerical solvers. This paper introduces an R package called rodeo to facilitate the implementation of ODE-based models. It addresses a standardized model notation and documentation as well as the automatic generation of efficient, solver-compliant Fortran or R source code. The package has the potential to make a multitude of environmental models, more comprehensible, reusable, and exchangeable. Highlights: An R-package 'rodeo' is introduced that facilitates environmental modelling based on ordinary differential equations (ODE). 'rodeo' imposes a well-known standard notation for simultaneous ODE with the stoichiometry matrix at its heart. Code generation allows the conceptual model (the set of ODE) to be separated from the implementation (computer program). The generated code (Fortran, R) can be used with existing numerical solvers, e. g. from R-packages 'deSolve' or 'rootSolve'. 'rodeo' comes with built-in support for 1-D partial differential equations being tackled with the numerical method-of-lines.